Penerapan Aplikasi Sistem Keuangan Desa (Siskeudes) di Desa Bukit Makmur Kecamatan Pinang Raya Kabupaten Bengkulu Utara - Karisma Juliana; Suratman; Yorry Hardayani (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2024)
The purpose of this study is to describe the causes of the suboptimal implementation of village financial system applications (siskeudes) in Bukit Makmur Village, Pinang Raya District, North Bengkulu Regency. This research uses BPKP guidelines on Siskeudes Application and Law Number 17 of 2003 concerning State Financial Management. The four main aspects that are the focus of this study are the planning stage, the budgeting stage, the administration stage, and the reporting stage. The method used is a descriptive qualitative method. Data collection techniques through observation, interviews, and documentation. The results of this study show that the implementation of the village financial system application (siskeudes) in Bukit Makmur Village, Pinang Raya District, North Bengkulu Regency has not been carried out optimally, because in the aspects of the planning stage and the administration stage, there are obstacles, namely the community does not understand about the Village RPJM, the development of RKP is not in accordance with the current village fund regulations and minutes and order letters have not been integrated into the siskeudes application.